ปัจจัยแห่งความสำเร็จของธนาคารขยะรีไซเคิล บ้านคำนางรวย ตำบลคำน้ำแซบ อำเภอวารินชำราบ จังหวัดอุบลราชธานี - จันทุมา พริมพรรณ (Area Based Development Research Journal, 2014)
การศึกษาครั้งนี้เป็นการวิจัยเชิงคุณภาพมีจุดประสงค์เพื่อ 1) ศึกษาสภาพการณ์และแนวทางการดำเนินงานธนาคารขยะรีไซเคิลบ้านคำนางรวย 2) ศึกษาการบริหารจัดการและปัจจัยความสำเร็จของการดำเนินงานธนาคารขยะรีไซเคิล บ้านคำนางรวย ตำบลคำน้ำแซบ อำเภอวารินชำราบ จังหวัดอุบลราชธานี โดยการเก็บข้อมูลจากการศึกษาเอกสาร การสัมภาษณ์เชิงลึก การสนทนากลุ่ม และการสังเกตแบบมีส่วนร่วม และไม่มีส่วนร่วมกับนายกเทศมนตรีตำบลคำน้ำแซบ ผู้จัดการธนาคาร ผู้ช่วยผู้จัดการธนาคาร เจ้าหน้าที่บัญชี เจ้าหน้าที่คัดแยก เจ้าหน้าที่ชั่งน้ำหนัก เจ้าหน้าที่ประชาสัมพันธ์และสมาชิก รวม 12 คน ผลการศึกษาพบว่า 1) ธนาคารขยะรีไซเคิลบ้านคำนางรวยจัดตั้งโดยนายนพคุณ ฉลาดแย้ม นายสิริรัฐ ธิมาและนายเฉลิมพล ทัดเทียม เปิดดำเนินการครั้งแรกเมื่อวันที่ 20 กรกฎาคม 2554 จนถึงปัจจุบัน โดยเปิดทำการในวันที่ 20 ของทุกเดือนตั้งแต่เวลา 06.00 น-15.00 น. มูลเหตุในการจัดตั้งธนาคารขยะฯเกิดจากความต้องการให้คนในชุมชนจัดการสิ่งแวดล้อมในชุมชนกันเอง โดยการสร้างจิตสำนึกให้ประชาชนในชุมชนรู้จักการลดปริมาณขยะ การคัดแยกขยะ เห็นขยะเป็นทรัพยากรใหม่ที่มีค่า ชุมชนมีรายได้เพิ่มทั้งยังเป็นการรักษาสภาพแวดล้อมให้น่าอยู่ กำไรที่ได้จากการบริหารงานธนาคารขยะรีไซเคิลบ้านคำนางรวยจะกลับคืนชุมชนในรูปแบบของสวัสดิการให้กับสมาชิกธนาคาร 2) ระบบการบริหารจัดการในรูปแบบของคณะกรรมการ คล้ายกับธนาคารทั่วไปและปัจจัยแห่งความสำเร็จของการดำเนินงานธนาคารฯ ประกอบด้วย (ก) การมีส่วนร่วมของประชาชนในชุมชนบ้านคำนางรวย มีส่วนร่วมคิด ร่วมตัดสินใจ ร่วมกันวางแผน ร่วมกันลงมือปฏิบัติงานและสมาชิกร้อยละ 85 มาประชุมทุกเดือน ปัจจุบันมีสมาชิกทั้งหมดจำนวน 141 ครัวเรือน (ข) ผู้นำและคณะกรรมการธนาคารฯ เป็นผู้ที่มีจิตอาสา เสียสละเวลามาปฏิบัติหน้าที่ มีความศรัทธา มีความเชื่อมั่น จริงจังในการทำงานทั้งที่ไม่มีค่าตอบแทน (ค) การบริหารจัดการ มีการวางแผน การจัดการ การประสานงาน การควบคุมงานอย่างเป็นระบบคณะกรรมการทุกคนในธนาคารขยะรีไซเคิลบ้านคำนางรวยสามารถปฏิบัติหน้าที่แทนกันได้ทุกตำแหน่ง (ง) มีหน่วยงานภาคีเครือข่ายทั้งภายในและภายนอกที่ให้การสนับสนุนด้านวัสดุอุปกรณ์และวิทยากร (จ) แรงจูงใจ มีสวัสดิการให้กับสมาชิก Success Factors in the Recycling Bank of Kham Ngnang Ruay in Kham Nam Saep Sub-district, Warinchamrap District, Ubon Ratchathani Province The current study is a qualitative research study which investigates 1) the situation of the recycle bank in Kham Ngnang Ruay village of Kham Nam Saeb Sub-district, Warinchamrap district, of Ubon Ratchathani province; 2) examine the administration of the bank and its success factors. The process of data collection involves documentary research, in-depth interviews, discussions of focus groups, and observations of both participants and non-participants in the research. Twelve participants in the research included the mayor of Kham Nam Saep Municipality, the bank manager, the accountant, staff dealing with waste separation, staff working on weighing the waste, staff specializing in public relations and the members of the bank. We found that 1) The bank was founded by Mr. Nopphakhun Chaladyaem, Mr. Sirirat Thima, and Mr. Chalermphon Thadthiem. It has been operated since July 20, 2011. It opens only on 20th of the month from 06.00 a.m. – 15.00 p.m. The needs to establish such a bank emerged from the needs of members of the community to deal with the environment of the community by themselves. Also members of the community want to raise awareness about environment by knowing how to reduce and separate waste. In this way, the community will eventually consider the waste as a newly valuable resource which can help to generate income for the community. At the same time, the community can protect the environment by doing this recycle activity themselves. The profits from operation of the the recycle bank will be returned to the community in a form of welfare for the bank members. We also found that 2) the administration system of the bank is similar to the administration of commercial or government banks. Factors which lead to the success of the bank include these. a) There is participation from residents of the Kham Ngang Ruay community. They have taken part in the process of brainstorming, making decisions, planning and administering the recycle bank. Moreover, a number of the community members attend the bank’s monthly meeting is at least 85% of the time. At present, there are 141 household members who are members of the bank. b) The leaders of the recycle project and the committee members of the bank are all volunteers who demonstrate the volunteer spirit and are dedicated to operating the recycle bank, even though they receive no pay from the bank. c) There is an effective and systematic administration from the point of view of planning, coordination and supervision. Every member of the bank is able to handle any of the responsibilities needed for the operation of the bank. d) There are both external and internal allied organizations which support the bank by providing it with materials, tools and staff members. e) There is an incentive in the form of community welfare for the members of the recycle bank.